2020
DOI: 10.1785/0220190253
|View full text |Cite
|
Sign up to set email alerts
|

The 2018 Geothermal Reservoir Stimulation in Espoo/Helsinki, Southern Finland: Seismic Network Anatomy and Data Features

Abstract: A seismic network was installed in Helsinki, Finland to monitor the response to an ∼6-kilometer-deep geothermal stimulation experiment in 2018. We present initial results of multiple induced earthquake seismogram and ambient wavefield analyses. The used data are from parts of the borehole network deployed by the operating St1 Deep Heat Company, from surface broadband sensors and 100 geophones installed by the Institute of Seismology, University of Helsinki, and from Finnish National Seismic Network stations. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(89 citation statements)
references
References 64 publications
7
82
0
Order By: Relevance
“…Our tests show that results from different choices of wave type, component, or frequency band can vary due to the sensitivity to different propagation effects. However, our observations generally agree with the vertical component P wave beamforming results obtained by Hillers et al (2020) using data from 6 M ≥ 1.1 events, which supports our comparison of the ADR and beamforming methods applied to the same S waveforms.…”
Section: 1029/2020gl090403supporting
confidence: 89%
See 2 more Smart Citations
“…Our tests show that results from different choices of wave type, component, or frequency band can vary due to the sensitivity to different propagation effects. However, our observations generally agree with the vertical component P wave beamforming results obtained by Hillers et al (2020) using data from 6 M ≥ 1.1 events, which supports our comparison of the ADR and beamforming methods applied to the same S waveforms.…”
Section: 1029/2020gl090403supporting
confidence: 89%
“…A total of ∼2900 induced seismic events were automatically detected by ISUH routine analysis. A subset of the 204 largest events was selected for magnitude and location estimation (Hillers et al, 2020; Supporting Information S1). We apply the method outlined in Section 2 to these events, which have a local magnitude range between M0.0 and M1.8 and source-receiver distances of 6-9 km.…”
Section: Data From the 2018 Espoo/helsinki Geothermal Reservoir Stimumentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid injection at depth in EGS stimulations and in wastewater disposal is commonly associated with induced seismicity (e.g., Ellsworth, 2013;Majer et al, 2012). Suc-cessful mitigation of an induced seismic hazard is important for public acceptance of geothermal projects, as there is significant concern related to the occurrence of larger induced earthquakes during previous EGS projects, e.g., in Basel and St. Gallen, Switzerland (e.g., Diehl et al, 2017), and most recently in Pohang, South Korea (Hofmann et al, 2019;Ellsworth et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Background natural seismicity is a common feature of geothermal systems (Hillers et al., 2020). Many studies revealed how the earthquakes occurring within a geothermal environment are tightly linked to fluid diffusion processes and their principal driving mechanism are transient fluid pressure changes in fractured rock volumes (Buizje et al., 2019; D'Auria et al., 2011; Hainzl et al., 2012; Norbeck & Shelly, 2018; Shapiro & Dinske, 2009; Tosha et al., 1998).…”
Section: Collected Datamentioning
confidence: 99%